The Effective Process Parameters of CO2 Adsorption on Peninsular Malaysia Shale Samples - Balogun, A.I. (Unconventional Resources Technology Conference (URTEC), 2021)
This study aims to investigate the effect of temperature and pressure on the adsorption capacity of selected shales samples from Terengganu peninsular, Malaysia using a volumetric technique at the temperature of 303.15, 318.15, 343.15K, and up to 100 bar pressure. Langmuir, Freundlich, Toth, and Sips equilibrium models are used to describe the adsorption measurement. Also, the sorption kinetics of the shale samples were modeled using Pseudo-first-order and Pseudo second-order respectively. Furthermore, physicochemical characteristics of the shale samples were conducted to determine the specific properties of the samples. From the experimental results, the shale samples were found to be rich in organic matter with total organic carbon (TOC) of between 2.0 and 3.0 wt indicating fair to good source rocks. The mineralogy of the shale samples via x-ray diffractogram (XRD) showed about 45 clay minerals and the FESEM surface morphology indicated the presence of clay minerals on the surface of the shale samples. These findings indicate the high potential capability of the studied shale samples for CO2 adsorption. Besides, functional groups such as the Si-O group, OH- group, and C=C groups were observed in the FTIR Spectra of the studied samples. In addition, the average pore size of 13.5 - 14.1 Nm, pore volume of 0.012 - 0.028 Cm3.gâ1, and surface area of 11.5 - 11.8 m2/g with a Type-II adsorption isotherm was obtained. These BET results indicated the presence of micropores and mesopores in the studied shale samples. Furthermore, it was observed that Langmuir, Freundlich, and Toth equilibrium models gave the best-fitted isotherm models that support monolayer, multilayer, and heterogeneous adsorption, respectively. Also, the k2 (diffusion) rate constant was observed to be greater than the k1 (chemisorption) rate constant for the analyzed shale samples at varying temperatures. That is, diffusion had a greater effect on CO2 adsorption than chemisorption. Conclusively, the results of this investigation indicate that pressure and temperature have a substantial influence on the CO2 adsorption capacity of shale. A pressure rise combined with a low temperature can result in more CO2 uptake, whereas a pressure reduction combined with a high temperature can result in lower CO2 uptake. Â© 2021 Unconventional Resources Technology Conference (URTeC)